2019
DOI: 10.1103/physrevc.99.031304
|View full text |Cite
|
Sign up to set email alerts
|

Description of shape coexistence in Zr96 based on the quadrupole-collective Bohr Hamiltonian

Abstract: Background: Experimental data on 96 Zr indicate coexisting spherical and deformed structures with small mixing amplitudes.Purpose: To investigate the properties of the low-lying collective states of 96 Zr based on the collective quadrupole Bohr Hamiltonian.Method: The β-dependent collective potential having two minima -spherical and deformed, is fixed so to describe experimental data in the best way.Results: Good agreement with the experimental data on the excitation energies, B(E2) and B(M 1) reduced transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…It turned out to be not the only doubly-closed shell nucleus to exhibit such shape coexistence structure. The nuclei 40 Ca, 56 Ni, but not only, have more recently indicated the appearance of bands pointing to strongly deformed structures [2][3][4][5]. The same, what was called shape coexistence, was observed in the heavy singleclosed shell nuclei such as the Pb isotopes and the Sn nuclei, with unambiguous indications of experimental evidence for the appearance of deformed bands (see [6] for a review).…”
Section: Introductionmentioning
confidence: 85%
“…It turned out to be not the only doubly-closed shell nucleus to exhibit such shape coexistence structure. The nuclei 40 Ca, 56 Ni, but not only, have more recently indicated the appearance of bands pointing to strongly deformed structures [2][3][4][5]. The same, what was called shape coexistence, was observed in the heavy singleclosed shell nuclei such as the Pb isotopes and the Sn nuclei, with unambiguous indications of experimental evidence for the appearance of deformed bands (see [6] for a review).…”
Section: Introductionmentioning
confidence: 85%
“…In recent years a number of experimental and theoretical studies of the spectroscopy of even-even Zr isotopes have been reported. Most recent experimental results have suggested shape coexistence in 96 Zr [3] and 98 Zr [4,5], a quantum phase transition around the neutron number N ≈ 60 [6,7], and γ-soft and triaxial shapes at 100,102 Zr [8]. Theoretical studies have generally confirmed the interpretation of these experimental findings [3,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 85%
“…Most recent experimental results have suggested shape coexistence in 96 Zr [3] and 98 Zr [4,5], a quantum phase transition around the neutron number N ≈ 60 [6,7], and γ-soft and triaxial shapes at 100,102 Zr [8]. Theoretical studies have generally confirmed the interpretation of these experimental findings [3,[9][10][11][12]. The neighbouring odd-A Zr nuclei have also been extensively studied in experiments.…”
Section: Introductionmentioning
confidence: 91%
“…To describe the shape of V (β) for 96 Zr we have defined in [57] several points fixing the positions of the spherical and deformed minima, the rigidity of the potential near its minima, and the height and width of the barrier separating two minima. Then we vary the positions of the selected points in order to get a satisfactory description of the experimental data.…”
Section: Hamiltonianmentioning
confidence: 99%
“…These investigations were based either on the nuclear Shell Model, or on the Hartree-Fock-Bogoliubov approach and on the Energy Density Functional . The second group includes studies based mainly on the phenomenological models [48][49][50][51][52][53][54][55][56][57][58]. Their aim was to achieve the best possible description of experimental data on Zr isotopes, fixing the model parameters for this purpose.…”
Section: Introductionmentioning
confidence: 99%